Ensino e aprendizagem da Matemática na modalidade EaD: um estudo de caso que utiliza metodologias ativasa - Santos, Giliane Souza de Matos dos (2020)
This study was initially motivated by concerns about the teaching and learning of Mathematics, in a first moment with classroom teaching and then, after some experiences, with teaching in Distance Education mode. After an exploratory research, in order to collect data to support the work, it was defined that this study would be a Case Study. For a period of six months, a Basic Mathematics Course offered in Distance Education mode which utilized Active Methodologies was accompanied. Based on these definitions, it was possible to elaborate the guiding question of this research “What reveals in teaching and learning of Mathematics in a Distance Education mode course and which uses Active Methodologies”? And as general objective “Verify the possible contributions and identify the difficulties in using Active Methodologies for teaching and learning of Mathematics in a Distance Education mode course”. To answer the guiding question, qualitative research was chosen, through inductive method and a case study. The theoretical framework is about Distance Education and Active Methodologies. The data collect and analysis followed what was proposed by Bogdan and Biklen, that is, a triangulation between the collected data, the theoretical framework and the researcher. From data collected on the Moodle Platform, on the WhatsApp Application, in the researcher’s logbook, focus groups and interviews, six categories emerged for analyzes with the potential to answer the guiding questions: Tutors, Students Participation, Dropout, Didactic Material, Synchronous and Asynchronous Interaction and Assessment. After analyzing the categories, the study reveals that teaching and learning in Distance Education mode when using active methodologies, good materials, qualification of teachers and tutors, can encourage students participation, contribute to reducing dropout and, consequently, to the quality of teaching and learning mathematics.